Nutrition and Physical Activity in Musculoskeletal Health - Ligia J. Dominguez; Nicola Veronese; Lee Smith; Francesco Saverio Ragusa; Giovanna Di Bella; Giuseppe Battaglia; Antonino Bianco; Mario Barbagallo (Endocrines)
A balanced diet and regular physical activity are essential for maintaining musculoskeletal health. Key nutrients such as calcium, vitamin D, and protein are especially important for preventing falls and fractures. While the benefits of these nutrients are well-established, other dietary components have not been studied as extensively. For instance, vegetables, which are rich in nutrients vital for muscle and bone health, play a crucial role in preventing falls and fractures. Over recent decades, a great emphasis has been given to the combinations of nutrients and foods in dietary patterns that may have synergistic or antagonistic effects. Despite the challenges in researching the impact of nutrition and physical activity on musculoskeletal health due to the extensive heterogeneity of the results, healthcare professionals should continue to promote healthy eating and regular physical activity, and these principles should be emphasized in public health initiatives. Ultimately, a sufficient and balanced diet, abundant in plant-based foods and low in processed or discretionary foods, along with consistent physical activity, remains the most effective strategy for the prevention of musculoskeletal issues. This article aims to review the updated literature of recent years on the links between nutrition and physical activity with bone and skeletal muscle health.